Leakage and rotordynamic coefficients of labyrinth-scallop seals - Izemenko, V.; Zahorulko, A.; Zahorulko, Yu. (Problems of Tribology, 2024)
Reducing leakages and improving the rotor-dynamic damping characteristics of annular seals is an essential problem of sealing technology. A whole range of damping seals are used to seal the shafts of turbomachines, such as honeycomb, hole pattern, pocket, and scallop seals. To reduce the cost and production time, the scallop seals are increasingly used. They showed quite good dynamic and leakage characteristics in the modernization of compressors in the chemical industry. Some designs of scallop seals are able not only to increase dynamic performance (additional use of swirl brakes in the form of semi-open scallops at the inlet) but also thanks to the hybrid design of the scallop and labyrinth seal made of PEEK material, which ensures a minimum clearance between the seal and the shaft, reduce leakages of pumped fluid. This paper presents the results of calculating the rotordynamic and flow rate characteristics of scallop and labyrinth-scallop seals depending on the operating parameters using computational fluid dynamics (CFD) methods. The CFD was used to calculate the hydrodynamic and rotordynamic characteristics of the seal with shaft whirl. The rotordynamic coefficients were obtained using the frequency excitation method. The obtained characteristics were compared with experimental data available from the literature for annular and labyrinth seals. The study confirmed the relatively low leakages, the high dynamic characteristics of the labyrinth-scallop seals, and the frequency dependence of the stiffness and damping coefficients. It has been confirmed that sickle-shaped scallops create obstacles to the circumferential flow of the working medium. Reducing the circumferential gas flow increases the hydraulic resistance in the grooves and simultaneously minimizes the circulation forces that create shaft whirl, increasing vibration